HOW TO IMPROVE STUDENTS’ READING SKILL IN CLASSES. - Surayyo Gafurovna, Ravshanova (Recent scientific discoveries and methodological research, 2024)
This article reviews to find out how the implementation of some techniques can improve the students’ reading skill and how the students’ responses to the use of those method in the teaching and learning process.